Host-guest system of 4-nerolidylcatechol in 2-hydroxypropyl-beta-cyclodextrin: preparation, characterization and molecular modeling - Soares, Lillian Amelia; Vasconcelos Borges Leal, Ana Flavia; Fraceto, Leonardo Fernandes [UNESP]; Maia, Elaine Rose; Resck, Ines Sabioni; Kato, Massuo Jorge; Gil, Eric de Sousa; de Sousa, Aparecido Ribeiro; da Cunha, Luiz Carlos; Rezende, Kennia Rocha (Springer, 2009)
The interaction of 4-nerolidylcatechol (4-NRC), a potent antioxidant agent, and 2-hydroxypropyl-beta-cyclodextrin (HP-beta-CD) was investigated by the solubility method using Fourier transform infrared (FTIR) methods in addition to UV-Vis, (1)H-nuclear magnetic resonance (NMR) spectroscopy and molecular modeling. The inclusion complexes were prepared using grinding, kneading and freeze-drying methods. According to phase solubility studies in water a B(S)-type diagram was found, displaying a stoichiometry complexation of 2:1 (drug:host) and stability constant of 6494 +/- A 837 M(-1). Stoichiometry was established by the UV spectrophotometer using Job's plot method and, also confirmed by molecular modeling. Data from (1)H-NMR, and FTIR, experiments also provided formation evidence of an inclusion complex between 4-NRC and HP-beta-CD. 4-NRC complexation indeed led to higher drug solubility and stability which could probably be useful to improve its biological properties and make it available to oral administration and topical formulations.
Keywords: 4-Nerolidylcatechol; 2-Hydroxypropyl-beta-cyclodextrin; Inclusion complex; (1)H-NMR and molecular dynamics